Microbiological diversity and functionality of a chronically hydrocarbon Contaminated soil post chemistry oxidation - Medina, Rocio (2015)
In situ chemical oxidation (ISCO) is increasingly used for the remediation of soil containing organic contaminants such as polycyclic aromatic hydrocarbons (PAH). However, the impact on the soil microbial community has not been thoroughly elucidated. The aim of the study was to analyze the effect of the ammonium persulfate application followed by a bioremediation process on the matrix,microbial community and the PAH removal of the soil.